Safety and Success of Lumbar Puncture in Young Infants: A Prospective Observational Study - Bedetti, Luca; Lugli, Licia; Marrozzini, Lucia; Baraldi, Alessandro; Leone, Federica; Baroni, Lorenza; Lucaccioni, Laura; Rossi, Cecilia; Roversi, Maria F.; D'Amico, Roberto; Iughetti, Lorenzo; Berardi, Alberto (Frontiers in Pediatrics, 2021)
Objective: This study aims to evaluate safety and success rates of lumbar puncture (LP) and to identify factors associated with adverse events or failure of LP in infants. Methods: This two-centre prospective observational study investigated infants younger than 90 days of age who underwent LP. Need for resuscitation oxygen desaturation (SpO2<90%), bradycardia and intraventricular hemorrhage were considered adverse events. LP failed if cerebrospinal spinal fluid was not collected or had traces of blood. Logistic regression analysis was used to evaluate whether corrected gestational age (GA), body weight at LP, position, and any respiratory support during LP affected SpO2 desaturation or failure of LP. Results: Among 204 LPs, 134 were performed in full-term and 70 in preterm born infants. SpO2 desaturations occurred during 45 (22.4%) LPs. At multivariate analysis, lower GA at LP (p <.001), non-invasive respiratory support (p 0.007) and mechanical ventilation (p 0.004) were associated with SpO2 desaturations. Transient, self-resolving bradycardia occurred in 7 (3.4%) infants. Two infants had intraventricular hemorrhage detected within 72 hours of LP. No further adverse events were registered. Failure of LP occurred in 38.2% of cases and was not associated with any of the factors evaluated. Conclusions: LP was safe in most infants. Body weight or GA at LP did not affect LP failure. These data are useful to clinicians, providing information on the safety of the procedure.